Estudio de la resistencia a la tracción, la deformación, la rigidez, de biopelículas de almidón de semilla de Persea americana Mill reforzadas con celulosa de la corona de Ananas comosus - Avalos Barreto, Diego Armando (2023)
In this research, the influence of the percentage by weight of cellulose and glycerin on the tensile strength, strain and stiffness of biofilms based on modified starch from the seed of Persea amerinaca Mill (avocado seed) was evaluated. Starch and cellulose were extracted by wet method and treatments (alkaline and acid) respectively. Biofilms were obtained by the solution fusion method. The percentages by weight of cellulose, as reinforcement, were 45, 50 and 55%; and glycerin, as a plasticizer, were 20, 25 and 30%; these dosages were used in the preparation of biofilms. For the tensile test, the guidelines of the ASTM D882- 12 standard were followed. The biofilms reached maximum tensile strength and stiffness values of 12.10 MPa and 54.05 MPa respectively; when the films were reinforced with 55% cellulose and plasticized with 20% glycerin; On the other hand, minimum tensile strength values of 7.15 MPa were obtained, when reinforced with 45% cellulose and plasticized with 30% glycerin, on the other hand, a minimum rigidity of 18.64 MPa was obtained, when reinforced with 50 % cellulose and plasticized with 25% glycerin. Regarding the maximum percentage strain was 42.64%, when it was reinforced with 50% cellulose and plasticized with 25% glycerin, on the other hand, the minimum percentage deformation was 21.95%, when it was reinforced with 45% cellulose and plasticized. with 20% glycerin. It has been concluded that biofilms, as the percentage by weight of cellulose increases up to 55%, the average values of tensile strength and stiffness increase, on the contrary, as the percentage by weight of glycerin increases up to a 25% tensile strength and stiffness decrease; regarding the percentage deformation the biofilms presented an inverse effect. This study aimed on expanding research on biofilms used as biodegradable packaging for the preservation of fruits, vegetables, and meats